ChemInform Abstract: Effects of Interstitial H and/or C Atoms on the Magnetic and Magnetocaloric Properties of La(Fe, Si)13‐based Compounds. Issue 48 (2nd December 2014) - Zhang, Hu; Hu, Feng Xia; Sun, Ji Rong; Shen, Bao Gen
Abstract Review: 54 refs.